HUBUNGAN KEKUATAN OTOT TUNGKAI DAN KESEIMBANGAN TERHADAP KEMAMPUAN TENDANGAN LURUS PADA SISWA TAPAK SUCI MADRASAH ALIYAH AL-FATAH NATAR - Aldianis Wirahuddin Akbar; Joan Siswoyo; Muhammad Fajril Rifaldo; Candra Kurniawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to examine the relationship between leg muscle strength and balance and the ability to perform straight kicks among Tapak Suci students at Al-Fatah Natar Islamic Senior High School. This research employed a quantitative method with a correlational approach. The sample consisted of 20 students selected using a total sampling technique. The instruments used included a leg muscle strength test, a balance test, and a straight kick ability test. Data were analyzed using Pearson Product Moment correlation and multiple correlation analysis at a significance level of 0.05. The results showed that: (1) there was a significant relationship between leg muscle strength and straight kick ability (rcalculated = 0.743 > rtable = 0.486), (2) there was a significant relationship between balance and straight kick ability (rcalculated = 0.707 > rtable = 0.486), and (3) simultaneously, there was a significant relationship between leg muscle strength and balance and straight kick ability (Fcalculated = 12.063 > Ftable = 3.592) with a contribution of 58.7%. In conclusion, leg muscle strength and balance play an important role in improving straight kick ability. Therefore, well-structured and integrated training programs are needed to enhance these components in order to support students’ performance in executing straight kicks.